2017
DOI: 10.3390/catal7010034
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Catalytic Selective Oxidation: Opportunities and Challenges

Abstract: Currently, and looking forward, there is an ever increasing demand to perform chemical transformations with optimized atom and energy efficiency. In parallel, there is also growing interest in diversification of chemical feedstocks from more traditional ones. For example, effective and economic transformation of biorenewable chemical feedstocks and shale-gas, are just two that can be highlighted. These targets are demanding and challenging, and the required shift in industrial production of energy and chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…However, using this kind of catalyst, the high operating temperatures cause the sintering and aggregation of silver particles, thus negatively affecting the formaldehyde yield. 29 In 1931, Adkin et al reported a new iron-based catalyst (Fe–Mo) to directly oxidize methanol into formaldehyde with an impressive catalytic performance. 30,31 The Fe–Mo-based approach for the production of FA proceeds according to eqn (2).CH 3 OH + 1/2 O 2 → CH 2 O + H 2 O Δ H = −159 kJ mol −1 …”
Section: Oxidative Conversion Of Methanolmentioning
confidence: 99%
“…However, using this kind of catalyst, the high operating temperatures cause the sintering and aggregation of silver particles, thus negatively affecting the formaldehyde yield. 29 In 1931, Adkin et al reported a new iron-based catalyst (Fe–Mo) to directly oxidize methanol into formaldehyde with an impressive catalytic performance. 30,31 The Fe–Mo-based approach for the production of FA proceeds according to eqn (2).CH 3 OH + 1/2 O 2 → CH 2 O + H 2 O Δ H = −159 kJ mol −1 …”
Section: Oxidative Conversion Of Methanolmentioning
confidence: 99%
“…In the case of the silver process, the catalyst undergoes agglomeration due to prolonged operation at high temperatures and needs to be replaced every 3 to 12 months. [14][15][16] The Formox process with a Fe-Mo catalyst also faces the problem of catalyst deactivation, which can be attributed to the volatilization of MoO 3 , formed due to the reaction of formaldehyde with the catalyst. [17][18][19][20] Thus, there has been a signicant research thrust in the synthesis of a new catalyst formulation that is low-cost, stable, and sustainable.…”
Section: Introductionmentioning
confidence: 99%